2021
DOI: 10.1371/journal.pone.0258703
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of morphological traits of wheat varieties at germination stage under salinity stress

Abstract: Salinity stress is one of the major plant growth-limiting factors in agriculture. It causes ionic imbalance, thus decrease the growth and yield attributes of crops especially wheat. Seedling stage is considered as one of the most sensitive stages under salinity stress. Survival of seeds at seedling stage can overcome the adverse impacts of salinity stress to some extent. Selection of salt tolerant varieties in seedling stage is considered as an effective strategy. Hence, current study was conducted to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The reduction in RL and SL under SS might be due to the reduced availability of water owing to osmotic stress caused by SS (Sultan et al, 2021). SS decreased the RFW which could be due to a reduction in the hydrolysis of food reservoirs and its movement to growing plant parts (Gholizadeh et al, 2021). The results indicated that SS imposed a negative impact on photosynthetic pigments (Table 3).…”
Section: Resultsmentioning
confidence: 96%
“…The reduction in RL and SL under SS might be due to the reduced availability of water owing to osmotic stress caused by SS (Sultan et al, 2021). SS decreased the RFW which could be due to a reduction in the hydrolysis of food reservoirs and its movement to growing plant parts (Gholizadeh et al, 2021). The results indicated that SS imposed a negative impact on photosynthetic pigments (Table 3).…”
Section: Resultsmentioning
confidence: 96%
“…Salinity impairs many plant functions, from the seed germination stage to final seed production; seedling emergence at the initiation phase of the lifecycle of plants is highly susceptible to salinity ( Naamala et al., 2022 ; Yaghoubian et al., 2022a ). However, once the plants are overcome the seedling stage, they are better able to cope with the adverse consequences of salinity stress ( Gholizadeh et al., 2021 ; Shah et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PLOS ONE Editors retract this article [ 1 ] because it was identified as one of a series of submissions for which we have concerns about authorship, competing interests, and peer review. We regret that the issues were not addressed prior to the article’s publication.…”
mentioning
confidence: 99%